Potret Remaja Urban dalam Novel Teenlit Berjudul Married With Senior karya Cintaprita - Nengsih Sri Rahayu Putri; Hasanuddin WS Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2023)
This article was written to explain and describe the portrait of urban youth in the teenlit novel entitled Married With Senior by Cintaprita. This study uses literary research with descriptive methods. Based on the results of research on the novel Married With Senior by Cintaprita, 22 data were found related to the portrait of urban youth in the novel. (1) The portrait of the fun personality of urban youth in Cintaprita's novel Married With Senior is described through addiction to online games and addiction to novels. (2) The portrait of the socio-economic position of an urban youth family in Cintaprita's novel Married With Senior is that urban teenagers are with upper-class social status. (3) The portrait of prestige urban youth recreation in Cintaprita's novel Married With Senior can be seen in the indicators of clothing used, namely wearing dresses, based on indicators of luxury cars and motorcycles, and places to visit restaurants and malls. (4) the portrait of the fun of urban youth playing groups in Cintaprita's novel Married With Senior can be seen by the fun of a group of teenage games. (5) The portrait of urban juvenile delinquency in the novel Married With Senior by Cintaprita can be seen urban youth described by Cintaprita namely wild racing, drinking wine and smoking.